2023
DOI: 10.1007/s10775-023-09584-0
|View full text |Cite
|
Sign up to set email alerts
|

Protean career processes in young adults: Relationships with perceived future employability, educational performance, and commitment

Abstract: Protean career processes of vocational identity awareness, career adaptability, and career agency have been hypothesized to mediate the relationships between protean career orientation and career-related outcomes. To date, the role of these process mechanisms has not been assessed directly in young adults, and little attention has been paid to educational outcomes, which are important career-related goals for young people on the way to their desired career. To address this gap, we tested this indirect-effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 97 publications
0
2
0
Order By: Relevance
“…In this context, Fernandez & Enache (2008) demonstrated that university students with stronger protean career attitudes exhibit a stronger sense of attachment to the workplace. Sinclair et al (2005) showed that commitment among working university students is associated with task and organisational citizenship behaviours (Kim et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, Fernandez & Enache (2008) demonstrated that university students with stronger protean career attitudes exhibit a stronger sense of attachment to the workplace. Sinclair et al (2005) showed that commitment among working university students is associated with task and organisational citizenship behaviours (Kim et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…capital; Donald et al, 2019), and subsequently increase their perceived employability (Baluku et al, 2021;Ho et al, 2023;Qenani et al, 2014). This hints at within-person changes, yet this has rarely been examined (Van Harten et al, 2021): Most studies focus on between-person differences rather than within-person changes (Ho et al, 2023;Kim et al, 2023). Taking a career development perspective, the relationship between career engagement and perceived employability is assumed to go in the opposite direction.…”
Section: Reciprocal Relationships Between Career Engagement and Perce...mentioning
confidence: 99%